A SINGLE-CENTER REAL-LIFE EXPERIENCE WITH FIRST-LINE DARATUMUMAB, BORTEZOMIB, CYCLOPHOSPHAMIDE, AND DEXAMETHASONE (DARA-VCD) IN AL AMYLOIDOSIS - Metban Mastanzade; Meryem Merve Ören Çelik; Simge Erdem; Mustafa Murat Özbalak; İpek Yönal Hindilerden; Mustafa Nuri Yenerel; Sevgi Kalayoğlu Beşışık (Hematology, Transfusion and Cell Therapy)
Case Report: Systemic amyloidosis results from the production of misfolded immunoglobulin light chains by monoclonal CD38+ plasma cells. These misfolded light chains form amyloid fibrils, which accumulate in various tissues and cause organ damage. Following the results of the Phase 3 ANDROMEDA study, where the addition of daratumumab, an anti-CD38 agent, to first-line treatment showed favorable outcomes, Dara-VCD has become a standard first-line therapy. In this study, we compared the outcomes of patients with AL amyloidosis who were treated with first-line Dara-VCD in our clinic to those treated with other triplet regimens. Methodology: Patient's data with AL amyloidosis followed between 2010 and 2024 were retrospectively reviewed from the institution's database. Two groups were established patients treated with Dara-VCD and those without Dara. The clinical characteristics and response criteria were compared using SPSS 21. Results: A total of 52 patients were included in the study, with a mean age of 60 ± 10 years for the entire group. There was no statistically significant difference in the demographic distribution between the groups (p = 0.003). The median follow-up period was 32 months (1-114 months). In 27 (51.9%) patients, cardiac involvement was present, and 26 (50%) had renal involvement. The stages of these involvements are summarized in Table 1. In the group treated without Dara, the triplet regimens were VCD (n=30), VRD (n=3), and VMP (n=2).Mortality was significantly lower in the Dara-VCD group. When evaluating responses, progression was only in 1 (9%) patient in the Dara group, whereas in 8 (32%) in the without Dara group.The overall survival was not statistically significant between the two groups (log-rank p=0.394). (Figure 1). Conclusion: We used Dara after Health Authority approval and reimbursement in our country. So, we get the opportunity to compare Dara-added VCD effectiveness to VCD or VRD as a real-life analysis. Dara-VCD resulted in a significantly lower rate of progression and mortality compared to those without Dara. The follow-up duration was shorter for comment on overall survival. Additionally, 10 patients without the Dara group, did receive daratumumab with VCD (n=5), or with other agents (n=5)). With this study, we documented from a real-life experience addition of daratumumab to the VCD regimen in first-line treatment reduces mortality and progression in AL amyloidosis.